The Apprehensions of Traditional Ulama towards Women’s Participation in Politics in Nigeria - Adebayo Rafiu Ibrahim (Al-Jami'ah: Journal of Islamic Studies, 2014)
Throughout the political history of Islam, women played significant political roles in the affairs of muslim states. This, however, has not been the situation in Nigeria where muslim women are skeptical about their involvement in politics, seeing it as an exclusively male domain. This has been so probably because of the voice of ulama against women’s participation in politics or the general belief that politics is a dirty game which is not meant for women. The big question then is why do Nigerian ulama resist women’s involvement in politics? Further, would muslims not stand the risk of losing their political potentiality should they remain indifferent to political participation by women? And, how do female muslim elites who have a flair for politics feel about their lack of political voice: would this not affect their spiritual or religious interests in the long run? This paper explores Islamic political history for the purpose of discovering the extent of muslim women’s involvement in politics, and the reasons for the non-involvement of muslim women in the nation’s politics from the viewpoint of the traditional ulama in the country. [Sepanjang sejarah Islam, wanita memainkan peran penting dalam politik di banyak negara muslim. Namun, hal ini tidak terjadi di Nigeria, karena wanitanya ragu terhadap peran mereka di kancah politik yang memang didominasi oleh para lelaki. Ini terjadi karena ulama menentang keterlibatan wanita di politik serta pandangan bahwa politik itu kotor dan tidak sesuai untuk wanita. Pertanyaannya kenapa para ulama menentang wanita berpolitik? Lalu, apakah mereka tidak rugi secara politis jika tidak peduli dengan partisipasi wanita? Bagaimana juga para wanita muslim itu tidak merasa kurang bersuara dalam politik: apakah ini tidak mempengaruhi spiritualitas dan kepentingan jangka panjang? Paper ini meneliti sejarah politik Islam terkait dengan peran wanita di politik, juga alasan kenapa mereka tidak terlibat menurut kaum ulama tradisional di Nigeria.]